Evaluation of sedentary women's ambulatory blood pressure and its relation to muscle strength - Ramires Alsamir Tibana; Denis César Leite Vieira; Vitor Tajra; Alexandre Vieira; Carlos Bainy Franz; Guilherme Borges Pereira; Jonato Prestes (Universidade de Fortaleza, 2012)
Objective: To compare the ambulatory blood pressure in women with different values of relative muscle strength. Methods: Data from 21 (aged 33.8±8.0 years) sedentary women from Vila Telebrasília was collected during the period of November 2010 to July 2011. The volunteers were submitted to the evaluation of the handgrip strength and ambulatory monitoring of blood pressure (AMBP) for a 72-hour period. Following the evaluation of handgrip strength to determine the absolute muscle strength, an adjustment in the body mass was made, in order to determine the relative muscle strength. Based on the relative value of muscular strength, the sample was divided into tertiles to compare systolic, diastolic and mean blood pressure during the periods of 24 hours, daytime and night-time, by using an one-way ANOVA, followed by Bonferroni test when appropriate, with a significance level of p<0.05. Results: Significant differences were found for systolic blood pressure between tertile 1 (99.3±12.2) and tertile 3 (106.8±11.1) in the night-time (P<0.05). Values of mean blood pressure were also significantly different between tertile 1 (70.2±6.3) and tertile 3 (80.3 ± 8.8) in the night-time (p<0,05). Conclusion: Women with higher relative muscle strength present lower values of blood pressure during night-time